Seroprevalence of Antibodies against Tick-Borne Pathogens in Czech Patients with Suspected Post-Treatment Lyme Disease Syndrome - Sloupenska, Kristyna; Dolezilkova, Jana; Koubkova, Barbora; Hutyrova, Beata; Racansky, Mojmir; Horak, Pavel; Golovchenko, Maryna; Raska, Milan; Rudenko, Natalie; Krupka, Michal (Microorganisms, 2021)
The hypothesized importance of coinfections in the pathogenesis of post-treatment Lyme disease syndrome (PTLDS) leads to the use of combined, ongoing antimicrobial treatment in many cases despite the absence of symptoms typical of the presence of infection with specific pathogens. Serum samples from 103 patients with suspected post-treatment Lyme disease syndrome were tested for the presence of antibodies to the major tick-borne pathogens Anaplasma phagocytophilum, Bartonella henselae/Bartonella quinatana, and Babesia microti. Although the presence of anti-Anaplasma antibodies was detected in 12.6% of the samples and anti-Bartonella antibodies in 9.7% of the samples, the presence of antibodies against both pathogens in the same samples or anti-Babesia antibodies in the selected group of patients could not be confirmed. However, we were able to detect autoantibodies, mostly antinuclear, in 11.6% of the patients studied. Our results are in good agreement with previously published studies showing the presence of a wide spectrum of autoantibodies in some patients with complicated forms of Lyme disease and post-treatment Lyme disease syndrome, but they do not reveal a significant influence of co-infections on the development of PTLDS in the studied group of patients.
Keywords: co-infection; seroprevalence; Lyme disease; ticks; Bartonella; post-treatment Lyme disease syndrome; Anaplasma; Babesia